O árbitro de vídeo : política, futebol e corpos em imagens (em movimento) - Galak, Eduardo (Arquivos em Movimento.)
The official use of the video referee (VAR) in the 2018 Russia World Cup allows to question some characteristics that seem not to have been argued. This essay is inserted in the controversial adoption of the VAR in football, condensing some ontological and axiological considerations that are demanded in football against the use of technology, as well as the articulations of technological actions on the body of who competes, arbitrates and attends, actions that are both aesthetic and political intervention. It is concluded that the justifications and desires of justice during the games only generate new expectations and new technological demands, beyond the official implementation of VAR. Such bureaucratization loses some human dimension of the unpredictable and liable to error that characterizes sports practices.